ANALISIS KEWAJIBAN PAJAK PERTAMBAHAN NILAI PADA PT. RPH TAHUN 2021 - Hiemawan, Rama Perdana; Widjaja, Purnamawati Helen (Jurnal Paradigma Akuntansi, 2025)
This study aims to analyze the calculation, payment, and reporting of Value Added Tax carried out by PT RPH during 2021 based on the regulations. The type of this research is a case study. The data used in this research are quantitative data such as Periodic VAT Returns for 2021 and Financial Statements for the 2021 period and the qualitative data are the information related to the company and the procedures for preparing Periodic VAT Returns. The analysis method used is descriptive method. The results of this study indicate that the calculations made by the company are correct but there are still delays in fulfilling the obligation to pay and report the VAT Periodic Tax Return made by PT. RPH.